Development and Evaluation of a Nature of Science-Based Online Course in Tenth-Grade Evolution - Kenneth Ian Talosig Batac; Voltaire Mallari Mistades (UM Purwokerto Press, 2022)
Worldwide, misconceptions and non-scientific notions about evolution are prevalent within academic circles. As online learning gains popularity because of the COVID-19 pandemic, it is crucial to identify practices that support learning in these contexts. Using the ADDIE instructional model, this study developed and evaluated a nature of science-based online course in evolution for tenth-grade junior high school students. Results revealed that the biology teachers considered the quality of pedagogies, resources, and delivery strategies in the online course excellent. Correspondingly, the students deemed the classroom climate in the online course exceptional in terms of instructor behaviors, course structure, course clarity, and student connectedness. The online course also helped them understand how evolution works through the videos and informative content and accept evolution by considering that several pieces of evidence and information support it and science and religion are not contradictory. Although the online course is good the way it is for most students, some of them provided recommendations for improvement. Overall, the students regarded the online course as recommendable because it is educational and manageable.